Investigation of Proline Amides and Pyridinium Salts as Catalyst for Direct Aldol Reactions in Water - Ozkan, Asli; Mavis, Murat Emrah; Aydogan, Feray; Yolacan, Cigdem (CHEM SOC PAKISTAN, 2014)
The catalytic potential of chiral proline amides and pyridinium salts in the aldol condensation in water was investigated. The aldol reactions of acetone with various aromatic aldehydes were carried out in water by using proline amide derivatives and pyridinium salts derived from chiral pyridine derivatives for the first time. The products were obtained in good yields within short reaction times.
Keywords: Aldol reactions; Green chemistry; Homogeneous catalysis; Phase-transfer catalysis; Proline amides; Pyridinium salts; ASYMMETRIC ORGANOCATALYSIS; INHIBITORS; ALDEHYDES; EFFICIENT; LIGANDS; KETONES; MEDIA; Chemistry